Timing and magnitude of drought impacts on carbon uptake across a grassland biome. Issue 10 (26th February 2023) - Felton, Andrew J.; Goldsmith, Gregory R.
Abstract: Although drought is known to negatively impact grassland functioning, the timing and magnitude of these impacts within a growing season remain unresolved. Previous small‐scale assessments indicate grasslands may only respond to drought during narrow periods within a year; however, large‐scale assessments are now needed to uncover the general patterns and determinants of this timing. We combined remote sensing datasets of gross primary productivity and weather to assess the timing and magnitude of grassland responses to drought at 5 km 2 temporal resolution across two expansive ecoregions of the western US Great Plains biome: the C4 ‐dominated shortgrass steppe and the C3 ‐dominated northern mixed prairies. Across over 700, 000 pixel‐year combinations covering more than 600, 000 km 2, we studied how the driest years between 2003–2020 altered the daily and bi‐weekly dynamics of grassland carbon (C) uptake. Reductions to C uptake intensified into the early summer during drought and peaked in mid‐ and late June in both ecoregions. Stimulation of spring C uptake during drought was small and insufficient to compensate for losses during summer. Thus, total grassland C uptake was consistently reduced by drought across both ecoregions; however, reductions were twice as large across the more southern and warmer shortgrass steppe. Across the biome, increased summer vapor pressure deficit (VPD) was strongly linked to peak reductions in vegetation greenness during drought. Rising VPD will likely exacerbate reductions in C uptake during drought across the western US Great Plains, with these reductions greatest during the warmest months and in the warmest locations. High spatiotemporal resolution analyses of grassland response to drought over large areas provide both generalizable insights and new opportunities for basic and applied ecosystem science in these water‐limited ecoregions amid climate change. Abstract : We combined remote sensing datasets of gross primary productivity and weather to assess the timing and magnitude of grassland responses to drought across two expansive ecoregions of the western US Great Plains biome. We found that (1) reductions to carbon uptake during drought consistently peaked in mid‐ and late June across both ecoregions, (2) cumulative (total) reductions in carbon uptake were twice as large across the more southern and warmer shortgrass steppe ecoregion, and (3) increased summer vapor pressure deficit was strongly linked to peak reductions in vegetation greenness during drought.